Protein-Protein Interactions Pathophysiological and Therapeutic Aspects: Volume II - Poluri, Krishna Mohan; Gulati, Khushboo; Tripathi, Deepak Kumar; Nagar, Nupur (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The second volume of the book-Protein-Protein Interactions (PPIs) provides an overview of various protein-protein interactions (PPIs) that are involved in various human diseases including cancer, neurodegenerative diseases, immune diseases, and inflammation. It summarizes the structure and ligand-based drug designing approaches for the discovery of small molecules that can inhibit PPIs in these diseases. The book discusses different computational and experimental tools that are used to determine the anomalous interactions underlying the diseases. Lastly, it also reviews the classical interactions between pathogens and hosts that are responsible for the pathophysiology of infectious diseases.
Chapter 1: Protein Networks in Human Disease -- Chapter 2: Protein-Protein Interactions in Cancer -- Chapter 3: Protein-Protein Interactions in Neurodegenerative Diseases -- Chapter 4: Protein-Protein Interactions in Immune Disorders and Inflammation -- Chapter 5: PPIs in Host-Pathogen Interactions -- Chapter 6: Drug Design methods to regulate protein-protein interactions -- Chapter 7: Small molecule inhibitors of Protein-Protein Interactions as Therapeutics.
Keywords: Bioinformatics; Life sciences; Medicine -- Research; Biology -- Research; Neurosciences; Bioinformatics; Life Sciences; Biomedical Research; Neuroscience